Eleocharis albalinsae (Cyperaceae), a new sedge species from northern and northeastern Brazil - Nunes, Clebiana De Sá; Maciel-Silva, Juliene De Fátima; Trevisan, Rafael; Gil, André Dos Santos Bragança (Phytotaxa, 2025)
During a recent taxonomic study of Cyperaceae in the Brazilian Amazon, a new species of Eleocharis (Cyperaceae) was discovered. It is described and illustrated here and compared with morphologically similar species. This new species is mainly characterized by its habit annual; culms circular in cross section; leaf sheath apex acute to attenuate, aristate; nutlet obovoid to ellipsoidal, greyish-white, distinctly 3–costate, surface smoothly reticulate (few times inconspicuous), epidermal cells hexagonal (sometimes irregularly shaped), and sparsely rough longitudinally. Although known from 11 specimens, most of which were collected in protected areas, both the area of occupancy and the quality of its habitat have declined, and subpopulations have become fragmented. We therefore recommend that the new species be classified as Endangered.